How They Claim The Victory: A Rhetorical Analysis On Indonesian Presidential Candidates’ Victory Speeches Within Pragma-Stylistic Framework - Hilarius Raditya Priambada Purba (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
ABSTRACT This study is a rhetorical analysis of the victory speech of Indonesian presidential candidates in a national election held on April 17th, 2019. This study aims to know the features of the pragma-stylistic mainly on speech act analysis as presented in the speeches related to winning claims by the candidates of the presidential election after the general election. This study attempts to identify and analyze the manifested speech within the pragma-stylistics framework, which is the speech act. This study assessed both presidential candidates’ victory speeches after the general election in Indonesia year 2019. The victory speeches were the speeches of Mr Joko “Jokowi” Widodo from Partai Demokrasi Indonesia Pembangunan (Indonesia Democratic Party of Struggle) and Mr Prabowo Subianto from Partai Gerakan Indonesia Raya (Great Indonesia Movement). The speech acts theory was employed to analyze the presented data in this study. The data were obtained from the great news platforms in Indonesia. The result showed that assertive appeared as the most frequent type used in the speeches. The result was reasonable due to the goal of the speech, which was to address the data obtained by both candidates and assure people that they deserved the place as the next Indonesian president. Keywords: Rhetorical analysis, Pragma-Stylistic Framework, Indonesian Presidential Candidates’ Victory Speeches